[PP.32.05] HYPERTENSION AND TYPE II DIABETES IN FIRST GENERATION CHINESE MIGRANTS SETTLED IN THE SOUTH OF EUROPE: THE CHINESE IN PRATO CROSS-SECTIONAL SURVEY. (September 2016) - Modesti, P.A.; Perruolo, E.; Calabrese, M.; Boddi, M.; Castellani, S.; Galanti, G.; Zhao, D.
Abstract : Objective: Despite concern about the epidemic of hypertension and type 2 diabetes mellitus in China, no data is available on health care needs of Chinese migrants settled in the South of Europe. In the last decades migration flows from China to Europe have been mainly directed towards Italy and Spain, and Chinese are now the third largest overseas-born population in Italy. Health needs of Chinese communities, are of special interest for health policies, strategies and plans. The objective of this study was to estimate prevalence of main risk factors among first-generation Chinese migrants living in Prato (Italy) in the age group 35 to 59 years. Design and method: Cross-sectional study. Population based samples of Chinese first-generation migrants living in Prato (n = 1200) and Italian adults (n = 291) were recruited. Measurements were performed by Chinese and Italian staff personnel. Primary outcome measure was hypertension, secondary measure being type 2 diabetes. Prevalence were based on direct standardization using the 2001 WHO World Standard Population. Associations with exposures (including age, gender, BMI, waist-to-hip ratio, education level, total cholesterol, triglycerides) were examined using logistic regression. Results: The prevalence of hypertension age-standardized according to the 2001 WHO population in the age range 35 to 59 years was 25.3% (95% Cl 24.3 to 26.4) among Chinese with 19.9% (95% Cl 18.0 to 21.8) among Italian participants (age- and sex-adjusted OR 1.57; 95 % Cl 1.10 to 2.2). Age standardized prevalence of type 2 diabetes was 12.9% (95% Cl 12.1 to 13.7) among Chinese and 6.6% (95% Cl 5.4 to 7.8) among Italian participants (age- and gender-adjusted OR 2.51; 95% Cl 1.55 to 4.08). In both Chinese and Italian adults, higher BMI was associated with hypertension, higher waist-hip ratio being associated with type 2 diabetes. Figure. No caption available. Conclusions: The limited information available on Chinese communities living in Europe highlights the strength of the present study. The high prevalence of main risk factors observed among first-generation Chinese migrants living in the South of Europe far from being a threat can be a turning point for implementation of specific health promotion programs.